196k views
1 vote
Put the equation in standard form.

y - 1 = -1/3 (x - 6)

User IFederx
by
4.5k points

1 Answer

1 vote

Answer:

x + 3y = 9

Explanation:

The equation of a line in standard form is

Ax + By = C ( A is a positive integer and B, C are integers )

Given

y - 1 = -
(1)/(3)(x - 6)

Multiply through by 3 to clear the fraction

3y - 3 = - (x - 6) ← distribute parenthesis by - 1

3y - 3 = - x + 6 ( add x to both sides )

x + 3y - 3 = 6 ( add 3 to both sides )

x + 3y = 9 ← in standard form

User Amavroudakis
by
5.8k points